ON THE TYPIFICATION OF BURMEISTERA (CAMPANULACEAE-LOBELIOIDEAE) AND THE IDENTITY OF B. CERATOCARPA VAR. DENTATA, B. IBAGUENSIS AND B. RIVINA (2015)
The genus Burmeistera, described by J. J. Triana in 1854, was typified with the species B. ibaguensis. The type specimen of this species consists of three fragments, two of which correspond to the type species and the third fragment belongs to B. rivina. Here we clarify the typification of the genus and the two species mentioned, and revise the descriptions of these species. In addition, a lectotype is here designated for B. rivina, and the name B. ceratocarpa var. dentata is subordinated to synonymy.